2010
DOI: 10.1177/1934578x1000500431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Essential Oil Formulations for Potato Sprout Suppression

Abstract: The concerns over safety and environmental impact of synthetic pesticides such as chlorpropham (CIPC) has stimulated interest in finding environmentally benign, natural sprout suppressants, including essential oils. The effects of Chenopodium ambrosioides and Lippia multiflora essential oils on sprout growth and decay of stored potatoes has been investigated. Formulations of essential oils with alumina, bentonite, or kaolin, both with and without Triton X-100 additive, were tested. These formulations have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Oosterhaven et al 1995a, b;Baydar and Karadogan 2003;Kleinkopf et al 2003;Eshel et al 2009;Campbell et al 2010;Owolabi et al 2010;TeperBamnolker et al 2010). In contrast to CIPC, the inhibition of post-harvest tuber sprouting by monoterpenes from essential oils appears not to be by interference with the cell cycle, as S-carvone (CAR) has no effect on flow cytometric histograms of potato cell nuclei (Oosterhaven et al 1995a).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Oosterhaven et al 1995a, b;Baydar and Karadogan 2003;Kleinkopf et al 2003;Eshel et al 2009;Campbell et al 2010;Owolabi et al 2010;TeperBamnolker et al 2010). In contrast to CIPC, the inhibition of post-harvest tuber sprouting by monoterpenes from essential oils appears not to be by interference with the cell cycle, as S-carvone (CAR) has no effect on flow cytometric histograms of potato cell nuclei (Oosterhaven et al 1995a).…”
Section: Discussionmentioning
confidence: 93%
“…Carvone is also a major constituent of caraway oil (54.9% S-carvone). The essential oils including those from peppermint (our work), spearmint (Teper-Bamnolker et al 2010) and other species (Owolabi et al 2010), as well as carvone, menthol, menthone, limonene and other monoterpenes are known to act as potato tuber bud sprout inhibitors (e.g. Vaughn and Spencer 1991;Oosterhaven et al 1995a, b;Baydar and Karadogan 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Owolabi et al [58,59] identified Lippia multiflora, Chenopodium ambrosioides, Cymbopogon citratus, and Zingiber officinale as promising sprout suppressants at temperatures 24 • C and above. L. multiflora and C. ambrosioides were found to suppress sprouting for up to 10 weeks in one cultivar [58].…”
Section: Emerging Essential Oils For Processing Potato Sprout Suppres...mentioning
confidence: 99%
“…DMN mode of action is still not clear, but it has been suggested that it may suspend/suppress normal cell division by inhibiting expression of genes that promote cell division or by enhancing expression of genes that inhibit cell division, which causes extension of dormancy period (Campbell et al 2010(Campbell et al , 2012Kleinkopf et al 2003). Other CIPC alternatives that have been found to suppress sprouting and sprout growth include natural compounds containing volatile monoterpenes and essential oils, such as cineole and eucalyptus oil (Vaughn & Spencer 1991, 1993Knowles & Knowles 2008), caraway oil (Gómez-Castillo et al 2013;Oosterhaven et al 1995;Şanli et al 2010;Teper-Bamnolker et al 2010), peppermint, spearmint, clove, and mint oils (Gómez-Castillo et al 2013;Kleinkopf et al 2003;Teper-Bamnolker et al 2010), menthe oil (Mehta & Kaul 2002), essential oils from aerial parts of Mentha spicata (Chauhan et al 2011) and essential oils from Chenopodium ambrosioides and Lippia multiflora (Owolabi et al 2010). Peppermint oil also has antioxidant and antimicrobial actions (Coleman et al 2001;Frazier et al 2004).…”
Section: Introductionmentioning
confidence: 99%